Geopolitical Conflict around the Climate Emergency: The Case of Deforestation in the Brazilian Amazon - Elsner, Zoe Anna (Latin American Report)
The 2019 United Nations (UN) Climate Action Summit was challenged by controversies around increasing deforestation in the Brazilian Amazon. Perspectives from the global community, the Brazilian government and indigenous and forest communities were heard, presenting a complex landscape of multi-scale approaches towards the rain forest. This paper takes the controversies made visible at the summit as a starting point to unravel the complex field of deforestation as an integrated part of the climate-change debate. Firstly, it will give some insights into the current situation in the Brazilian Amazon and the conflicting perspectives. Then it will explore theories that have emerged around climate justice and equity, leading to a call for “burden sharing” aimed at assistance in climate matters for the Global South. It will continue by showing such efforts and will comment on their insufficiencies. It will use relevant literature to showcase how the example of the Brazilian Amazon is representative of a complex set of systems created by the Global North, set on their agenda. These multifaceted theories show a complex field—with a multitude of stakeholders—that is hard to negotiate. In this light, the text concludes that the current discourse, vilifying Bolsonaro, falls short of adequately addressing the complexity of the issue.